Women’s Access to Justice as a Result of State Repressiveness in Indigenous Land Conflict Areas - Salamah, Ummu; Mustakim, Mustakim; Rumadan, Ismail (Journal of Posthumanism, 2025)
This research aims to examine the issue of access to justice for women in the context of customary land conflicts in Indonesia, where state repressive measures are often a significant barrier. The background shows that customary land conflicts have a direct impact on women, who are the most vulnerable when they lose access to natural resources. The problems studied include women's inability to access justice due to state action, the obstacles they face, and the effectiveness of state policies in providing protection for women. The research method used is empirical juridical with legal analysis and field observation, through legal data collection and direct interviews with women, activists, and relevant officials. The conclusion of this study states that state repressive actions, social norms, and legal discrimination worsen the conditions of access to justice for women. Although there are policies that guarantee protection for women, their implementation is often minimal and does not cover their needs in conflict situations. Recommendations include policy reform, increasing women's participation in decision-making, and creating an enabling environment for women's rights. This research emphasises the importance of empowering women in accessing justice to achieve more inclusive and sustainable development.